Antibacterial Properties of Clay Layers Silicate: A Special Study of Montmorillonite on Cotton Fiber - Sadeghian Maryan, Ali; Montazer, Majid; Rashidi, Abousaied; Karim Rahimi, Mohammad (Asian Journal of Chemistry, 2012)
Many antibacterial compounds, with different natural and synthetic structures, have been developed during past decades. This paper reports the antibacterial properties of silicate clay (montmorillonite) and cotton treated with montmorillonite clay. Different concentration of montmorillonite clay and modified montmorillonite clay with quaternary ammonium salt (A-MMT) were applied to cotton fabric. The antibacterial activity of clay and treated cotton with clay were evaluated according to AATCC 100. Antibacterial effects of montmorillonite clay with quaternary ammonium salt and montmorillonite clay were satisfactory against two types of bacteria: Staphylococcus aureus and Escherichia coli. Also, the same results on the loaded cotton with montmorillonite clay with quaternary ammonium salt and montmorillonite clay were obtained.